ANALYSIS OF AFFICSIAL QUALITY MAKING IN DARY LANGUAGE (Academicia Globe: Inderscience Research, 2021)
In recent years, the comprehensive development of the Dari language has become noticeable, during which time there have been tangible changes in all its fields. And in this regard, the study of the questions of the ways of forming, developing, and improving the Dari language, substantiating the reasons, regularities, and possibilities of this process, as well as determining the principles of word-formation, is becoming increasingly essential. This, in turn, points to the need for a separate study of the Dari language directly based on its materials.